2015
DOI: 10.4054/demres.2015.32.12
|View full text |Cite
|
Sign up to set email alerts
|

Working with teams of "insiders"

Abstract: BACKGROUNDThe convergence of two qualitative methodological strategies -working in "teams" and with "insiders" -can facilitate access, efficiency, and insights into research questions of interest to demographers. Even though this approach is becoming more common among population researchers in the Global South to address a range of research questions, little has been published that describes the method and critically assesses its strengths and weaknesses. OBJECTIVEWe draw on three projects embedded in the Agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Empathy and personal growth. (Emotional) safety of researchers in sensitive studies is slowly gaining visibility [7], but seldom extends to CBRs [6,33]. As an embodied experience, participatory violence and mental health research requires emotional connectedness and bearing witness to myriad forms of trauma with implications for wellbeing [7,34,35].…”
Section: A Learning About Research Violence and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Empathy and personal growth. (Emotional) safety of researchers in sensitive studies is slowly gaining visibility [7], but seldom extends to CBRs [6,33]. As an embodied experience, participatory violence and mental health research requires emotional connectedness and bearing witness to myriad forms of trauma with implications for wellbeing [7,34,35].…”
Section: A Learning About Research Violence and Mental Healthmentioning
confidence: 99%
“…Participatory methods, which rely heavily on community-based researchers (CBRs), are growing in popularity to deliver such critical research, bringing rewards and challenges for research teams and affected communities [2,3]. While research institutions, funders, and ethics bodies increasingly encourage practice standards to support wellbeing among participants in (participatory) violence and mental health studies [4,5], comparable efforts to understand and advocate for attending to the role-specific needs of researchers, and especially CBRs, are lacking [6,7]. Given the legacy of imbalanced power relations "in the creation of global health, and how [it] persists in the field" [8, p1059], concerted efforts to value the expertise and capacities of local collaborators like CBRs and communities are paramount in contemporary global health research [2].…”
Section: Introductionmentioning
confidence: 99%
“…Research teams that include insiders and outsiders can provide important advantages related to maximising trustworthiness of findings whilst supporting participant wellbeing (Schatz et al, 2015; Thomas et al, 2000). The different social positions of each member of the research team meant each could provide participants with different types of support.…”
Section: Beneficencementioning
confidence: 99%
“…The concept of 'insiders' refers to the position of peers who are working within one's own cultural or social community (Vaughn et al, 2018). The caseanalysis showed that Abby was perceived by her peers as more approachable and reliable due to her insider status, knowledge and shared experiences and became the intermediary between FabLab team and her own community of youth (work) organizations (Guta et al, 2013;Schatz et al, 2015;Vaughn et al, 2018 However, this intermediary role works in two ways: Abby shares the perspective of the youth (work) organizations with the FabLab, but also shares the ideas and opportunities of the FabLab with her peers of the youth (work) organizations. For instance Abby stated that:…”
Section: Community Of Peersmentioning
confidence: 99%